me ajudem por favor..não precisam responder td
Anexos:
![](https://pt-static.z-dn.net/files/d3b/bad3a3a206ddcbb6d20b187041eb80c0.jpg)
Soluções para a tarefa
Respondido por
0
Resolução:
a) ㏒₅N = 3 ⇒ N = 5³ ⇒ N = 125
b) ㏒₂N = 8 ⇒ N = 2⁸ ⇒ N = 256
c) ㏒₂N = -9 ⇒ N = 2⁻⁹ ⇒ N = 1/512
d) ㏒√3 N = 2 ⇒ N = (√3)² ⇒ N = 3
2) a) ㏒ₐ 81 = 4
ₐ⁴ = 81
ₐ⁴ = 3⁴
a = 3
b) ㏒₉ₐ√27 = 1/2
![(9a)^ \frac{1}{2} = \sqrt{27} (9a)^ \frac{1}{2} = \sqrt{27}](https://tex.z-dn.net/?f=+%289a%29%5E+%5Cfrac%7B1%7D%7B2%7D+%3D+%5Csqrt%7B27%7D++)
![9 \frac{1}{2}.a \frac{1}{2} =3 \sqrt{3} 9 \frac{1}{2}.a \frac{1}{2} =3 \sqrt{3}](https://tex.z-dn.net/?f=9+%5Cfrac%7B1%7D%7B2%7D.a+%5Cfrac%7B1%7D%7B2%7D+%3D3+%5Csqrt%7B3%7D++)
![a \frac{1}{2} = \frac{3 \sqrt{3} }{ \sqrt{9} } a \frac{1}{2} = \frac{3 \sqrt{3} }{ \sqrt{9} }](https://tex.z-dn.net/?f=a+%5Cfrac%7B1%7D%7B2%7D+%3D+%5Cfrac%7B3+%5Csqrt%7B3%7D+%7D%7B+%5Csqrt%7B9%7D+%7D+)
![\sqrt{a} = \frac{3 \sqrt{3} }3} \sqrt{a} = \frac{3 \sqrt{3} }3}](https://tex.z-dn.net/?f=+%5Csqrt%7Ba%7D+%3D+%5Cfrac%7B3+%5Csqrt%7B3%7D+%7D3%7D+)
![a= \frac{3^2.3}{3^2} a= \frac{3^2.3}{3^2}](https://tex.z-dn.net/?f=a%3D+%5Cfrac%7B3%5E2.3%7D%7B3%5E2%7D+)
![a = 3 a = 3](https://tex.z-dn.net/?f=a+%3D+3)
bons estudos:
a) ㏒₅N = 3 ⇒ N = 5³ ⇒ N = 125
b) ㏒₂N = 8 ⇒ N = 2⁸ ⇒ N = 256
c) ㏒₂N = -9 ⇒ N = 2⁻⁹ ⇒ N = 1/512
d) ㏒√3 N = 2 ⇒ N = (√3)² ⇒ N = 3
2) a) ㏒ₐ 81 = 4
ₐ⁴ = 81
ₐ⁴ = 3⁴
a = 3
b) ㏒₉ₐ√27 = 1/2
bons estudos:
Respondido por
1
Vejamos:
Equivalência fundamental
㏒αᵇ = с ⇒ entâo: b = a^c.
Nesses casos teremos:
2º - a) ㏒5ⁿ = 3 ⇒ n = 5³ ⇒ n = 125
b) ㏒₂ⁿ = 8 ⇒ n = 2⁸ ⇒ n = 256
c) ㏒₂ⁿ = -9 ⇒ n = 2⁻⁹ ⇒ n = 1/2⁹ ⇒ n = 1/512
d) ㏒₍√3 ₎ⁿ = 2 ⇒ n = (√3)² ⇒ n = 3
3º - a) ㏒α⁸¹ = 4 ⇒ α⁴ = 81 ⇒ a = ⁴√81 ⇒ a = 3
b) ㏒9α^√27 = 1/2 ⇒ 9a^1/2 = √27 ⇒ √9a = √27. Daí: 9a = 27 ∴ a = 27/9 = 3
Equivalência fundamental
㏒αᵇ = с ⇒ entâo: b = a^c.
Nesses casos teremos:
2º - a) ㏒5ⁿ = 3 ⇒ n = 5³ ⇒ n = 125
b) ㏒₂ⁿ = 8 ⇒ n = 2⁸ ⇒ n = 256
c) ㏒₂ⁿ = -9 ⇒ n = 2⁻⁹ ⇒ n = 1/2⁹ ⇒ n = 1/512
d) ㏒₍√3 ₎ⁿ = 2 ⇒ n = (√3)² ⇒ n = 3
3º - a) ㏒α⁸¹ = 4 ⇒ α⁴ = 81 ⇒ a = ⁴√81 ⇒ a = 3
b) ㏒9α^√27 = 1/2 ⇒ 9a^1/2 = √27 ⇒ √9a = √27. Daí: 9a = 27 ∴ a = 27/9 = 3
descart:
De nada!
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
ENEM,
1 ano atrás
Matemática,
1 ano atrás